Using a systems approach for drought risk financing solutions in Senegal - Banerjee, Rupsha R.; Chan, Derek; Houessionon, Prosper; Paliwal, Ambica; Alulu, Vincent; Galgalo, Diba; Shikuku, Kelvin Mashisia; Ouédraogo, Issa (International Livestock Research Institute, 2022)
The index-based livestock insurance (IBLI), since the time it was launched in 2010 in the arid and semi-arid lands of Kenya and Ethiopia, has evolved into drought risk financing solutions (DRFS). This evolution is characterized by development from a micro product implemented, as potential social protection tools, to a regional level de-risking instrument for pastoralists in the Horn of Africa. There have also been demands for DRFS to rise to several other challenges such as conflict, access to health and market services (feed, fodder) that are being faced in the drylands of Africa. The rapidly changing contexts and the associated challenges mean that the introduction of DRFS requires careful assessment to ensure the necessary pre-conditions are in place for optimal positive impact. Assessment would have to consider incentivizing the private sector from the beginning for investment in these areas, management of natural resources, better access to services (financial and non-financial), gender inclusion and social equity. Such an approach is important for developing resilience not just against challenges related to climate change but the ever-changing dynamics in these complex environments.